Deportation as Rescue: How Danish Society Responds to the Figure of the Migrant Sex Worker - Tendler, Hannah (Culture and History: Student Research Papers, 2022)
This article interrogates the conceptualisation of the figure of the migrant sex worker in Danish society. Reflecting on laws, policies and public attitudes towards sex work in the European context, it considers the tangible impacts on the rights of migrants selling sex. Delving deeper into public political debates on sex work, it finds that within Danish society, the migrant sex worker is rarely conceptualised as a worker. Instead, she is predominantly perceived to be a victim. This keeps the figure of the migrant sex worker in the realm of the exceptional and justifies the use of deportation as ‘rescue’.